Early events of root colonization in castor by the biocontrol agent Trichoderma: Early events of root colonization in castor by the biocontrol agent Trichoderma - K B DURGA BHAVANI; R BHUVANESWARI; VELU MANI SELVARAJ; R D PRASAD; V DINESH KUMAR (Journal of Oilseeds Research, 2020)
The colonization of castor roots by the biocontrol agent Trichoderma has been studied in a time series experiment. The results showed penetration and colonization of castor roots by Trichoderma within 48 hours post inoculation. Microscopy studies established that the colonization was restricted to cortical cells of the roots and during this interaction there were architectural changes in the cell wall of the host cells.